Islamic education teachers’ strategies in countering digital radicalism among students at smk 17 parakan - Ahmad Saichu; Luluk Ifadah; Ana Sofiyatul Azizah; Tsabita Nur Azizah; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2023)
The phenomenon of the spread of radical ideologies through digital media has become a real challenge in the field of education, particularly among students who lack a mature ideological filter. Students at SMK 17 Parakan are among the vulnerable groups exposed to exclusive and intolerant religious narratives disseminated through various digital platforms. This study aims to identify the forms of digital radicalism circulating among students, examine the challenges faced by Islamic Education (PAI) teachers in addressing it, and explore the strategies used to instill the values of religious moderation.This research employed a phenomenological approach to understand the lived experiences of PAI teachers in dealing with digital radicalism, using a qualitative case study design. Primary data were obtained from PAI teachers, while secondary data were sourced from books, school archival documents, and scholarly journals. Data were collected through in-depth interviews, observation, and documentation. The data analysis process consisted of data collection, reduction, display, and conclusion drawing/verification. Data triangulation, involving sources and methods, was used to ensure validity.The findings reveal that forms of digital radicalism recognized by students include symbols of violence, intolerance toward diversity, and exclusive religious doctrines. PAI teachers face challenges such as limited digital literacy, social and psychological pressures, and curriculum content that is less responsive to contemporary religious issues. Strategies implemented include strengthening digital literacy, integrating counter-radicalism content contextually into teaching materials, and internalizing the values of religious moderation such as tawassuth (moderation), tasamuh (tolerance), and tawazun (balance).The study concludes that adaptive and reflective teacher strategies, grounded in the direct experiences of teachers and students, can foster critical awareness of digital radicalism and cultivate inclusive religious character. Utilizing digital media as a means of promoting moderate religious education serves as an important innovation in contextual learning in the digital era.